2019
DOI: 10.1038/s41413-019-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: a missing link in osteoporosis

Abstract: Osteoporosis is a systemic disease that results in loss of bone density and increased fracture risk, particularly in the vertebrae and the hip. This condition and associated morbidity and mortality increase with population ageing. Long noncoding (lnc) RNAs are transcripts longer than 200 nucleotides that are not translated into proteins, but play important regulatory roles in transcriptional and post-transcriptional regulation. Their contribution to disease onset and development is increasingly recognized. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 199 publications
(281 reference statements)
1
72
0
Order By: Relevance
“…The osteoblast differentiation is precisely controlled by a variety of intracellular signaling pathways. In recent years, emerging evidence has demonstrated that epigenetic pathways, including long noncoding RNAs (lncRNAs) [3], are playing critical roles in regulating osteoblast differentiation and thus considered as a new focus point in bone research.…”
Section: Introductionmentioning
confidence: 99%
“…The osteoblast differentiation is precisely controlled by a variety of intracellular signaling pathways. In recent years, emerging evidence has demonstrated that epigenetic pathways, including long noncoding RNAs (lncRNAs) [3], are playing critical roles in regulating osteoblast differentiation and thus considered as a new focus point in bone research.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed that lncRNAs participate in the initiation and progression of several types of bone diseases including bone tumors (27), osteoarthritis (OA) (28,29), osteoporosis (30,31), RA (32) and ankylosing spondylitis (AS) (33). MEG3 has been shown to be involved in the development of the all these bone diseases, as shown in Table II. MEG3 and bone tumors.…”
Section: Roles Of Lncrna Meg3 In Bone Diseasesmentioning
confidence: 95%
“…Recently, lncRNAs have emerged as novel regulatory markers of osteoporosis (30,31). Osteoporosis is a systemic skeletal disorder characterized by low bone mass, and is associated with an increase in the risk of bone fracture (59).…”
Section: Meg3 and Osteoporosismentioning
confidence: 99%
“…For these reasons, these lncRNAs were defined as competing endogenous RNAs (ceRNAs) ( Figure 1). lncRNAs have been associated with the development of osteoporosis, and some authors proposed their use as a diagnostic and therapeutic tool for osteoporosis [73][74][75][76][77][78]. For example, X-inactive-specific transcript (Xist) RNA has been described to inhibit osteogenic differentiation bone marrow mesenchymal stem cell [79].…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%